An insight into volatile and non‐volatile compounds of Chinese horsebean‐chili‐paste meju produced by natural brewing and temperature‐controlled brewing methods. (19th October 2020) - Tan, Xinyi; Lu, Yunhao; Lin, Xin; Ni, Nan; He, Qiang; Chi, Yuanlong
Abstract: BACKGROUND: Chinese horsebean‐chili‐paste (CHCP) is a traditional fermented condiment in China, known as 'the soul of Sichuan cuisine'. The horsebean‐to‐meju phase in its preparation is important for CHCP production and contributes significantly to its taste and odor. In this study, a comprehensive flavor compound profiling analysis of the naturally brewed horsebean meju (NBHM) and the temperature‐controlled brewed horsebean meju (TCBHM) was performed with two‐dimensional gas chromatography time‐of‐flight mass spectrometry (GC × GC‐TOFMS), and the analysis of physicochemical characteristics and free amino acids. Their aroma‐active components and characteristic flavor compounds were evaluated. The flavor compounds responsible for differentiating NBHM and TCBHM were also determined based on the Fisher ratio and principal component analysis. RESULTS: The pH and the reducing sugar and amino‐acid nitrogen content of NBHM were 5.38, 64.43, and 5.76 g kg −1, respectively, whereas those of TCBHM were 5.13, 29.20, and 7.43 g kg −1 . A total of 356 volatiles were identified from 2571 compounds, and 257 volatile compounds were identified in NBHM compared to 322 volatiles in TCBHM. These two horsebean mejus (HMs) exhibited a similar proportion profile for 30 aroma‐active compounds. Benzoic acid ethyl ester, 4‐ethyl‐2‐methoxy‐phenol and argnine were determined to be characteristic flavor components for NBHM, while 1‐(2‐furanyl)‐ethanone, 2, 6‐dimethyl‐pyrazine, threonine, valine and tyrosine were specific to TCBHM. CONCLUSION: Temperature‐controlled brewed horsebean meju possessed better physicochemical and flavor characteristics than NBHM. The temperature‐controlled brewing technique in CHCP production can be used as a promising alternative to the traditional natural brewing method. © 2020 Society of Chemical Industry